The impact of AI-based Content Personalization on Consumer Behavioron Digital News Platforms - Insania Juliani; Bq. Hairunnisa; Aisyah Aryandani (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2025)
The rapid advancement of artifical intelligence (AI) has significantly transformed the landscape of digital marketing. One of the most prominent applications of AI in this domain is content personalization, which enables bussines to deliver tailored experiences based on individual user preferences, behaviors, and online interaction. This study aims to examine the impact of AI-driven contentpersonalization on consumer behavior, focusing specifically on aspects such as engagement, satisfaction, and costumer loyality. A quantitative research approach was employed through an online survey conducted with 100 active users of digital platforms that incorporate personalzed content features. The survey findings indicate that a substantial portion of respondents believe personalized content enhances their overall browsing experience, increases relevance, and fosters a stronger emotional connection with the platform. Specifically, 72% of respondents agreed that personalized content made them feel more valued and understood by the service provider, while 65% expressed a higher likelihood of returning to platforms that consistently offer tailored recommendations. These results suggest that AI-based personalization can significantly influence consumer decisionmaking by creating more relevant and engaging interactions, ultimately encouraging long-term brand loyalty. However, the study also reveals a growing concern among users regarding data privacy. A portion of the respondents expressed discomfort over the extensive collection and usage of personal information required for such personalization, highlighting the ethical and regulatory challenges that must be addressed. Therefore, while AI personalization offers clear benefits in enhancing marketing strategies and user experience, it also demands careful consideration of user consent and data protection policies. In conclusion, the integration of AI personalization in digital marketing can serve as a powerful tool for improving consumer engagement and satisfaction. Yet, companies must strike a balance between personalization and privacy to maintain trust and transparency. Future research could explore the long-term behavioral effects of personalization and examine cross-cultural differences in user responses to AI-driven marketing.